Update on Obesity: Induced Inflammation to Cause Cardiometabolic Diseases - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Obesity incidence has risen dramatically during the last 50 years, reaching epidemic proportions. Obesity's growing prevalence, as well as its numerous metabolic and cardiovascular problems, poses a danger to human health and lifespan across the world.CONTENT: Numerous studies have shown that obesity causes inflammation, and suggest that inflammation may have a causal role in the development of insulin resistance, defective insulin secretion, and energy homeostasis disturbance. Obesity-induced inflammation is different from other inflammatory models because it includes tonic activation of the innate immune system, which has a long-term influence on metabolic balance. Inflammation can cause tissue damage by causing maladaptive responses such as fibrosis and necrosis. Obesity-induced inflammation is unique since it affects a variety of organs, including the adipose tissue, pancreas, liver, skeletal muscle, heart, and brain. These characteristics of obesity-induced inflammation make it difficult to decipher the underlying processes and how they affect metabolic systems.SUMMARY: The disruption of energy homeostasis caused by a positive energy balance is most likely the first trigger of metabolic inflammation, and the initial adaptive response aim to relieve the anabolic pressure caused by obesity. However, over time, this adaptive reaction becomes maladaptive, and the persistence of inflammation shows that the initial response has failed. The inflammation affects so many organ systems during obesity, and to develop novel treatment methods, a greater knowledge of the process was needed.KEYWORDS: obesity, inflammation, diabetes mellitus, non-alcoholic fatty liver disease, cardiovascular diseases, heart failure